Impact Of Ramadan Focused Education Program On Hypoglycemic Risk And Metabolic Control For Patients With Type 2 Diabetes - Tourkmani, Ayla Mhd. Dadou (2017)
Ramadan fasting is associated with significant impact on glycemic control and patient safety among patients with type 2 diabetes (T2D). The burden of the problem is high in Saudi Arabia due to the high prevalence of diabetes. The risk can be aggravated by hot weather and long fasting duration during Ramadan in Saudi Arabia. Current guidelines recommend counseling and educating patients with T2D before Ramadan.